A low-density carbon aerogel material and a method for preparing the same
Patent Information
- Application Number
- CN202611507217.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]鉴于上述的分析,本发明旨在提供一种低密度碳气凝胶材料及其制备方法,用以解决现有技术中为提升力学性能而显著增加密度、工艺复杂难以工业化以及低密度下力学性能与隔热性能难以协同优化等问题中的至少一个
(1)本发明通过将两种或两种以上溶剂复配,以对数加和方式量化复配溶剂的整体极性并控制在适宜范围内,实现对溶剂极性的定量调控。当复配溶剂极性处于所述适宜区间时,体系落入旋节线内热力学不稳定区,微小浓度涨落自发驱动体系分相,形成高度互联的双连续互穿网络结构,使骨架颗粒显著细化、分布均匀,压缩强度和结构完整性得到根本性提升。现有技术多停留于现象观测层面,未建立定量调控手段并应用于低固含量酚醛体系。本发明通过极性量化评价与精确控制,在不显著增加密度、不引入复杂工艺的前提下,实现了低密度碳气凝胶综合性能的突破。
Smart Images

Figure CN123002825A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermal protection materials technology, and in particular to a low-density carbon aerogel material and its preparation method. Background Technology
[0002] Carbon aerogels, due to their low density, high porosity, and excellent high-temperature thermal stability, have broad application prospects in aerospace thermal protection, adsorption filtration, and other fields. However, the inherent high porosity and bead-like carbon particle overlap structure of carbon aerogels result in high intrinsic brittleness, low mechanical strength, and difficulty in molding large-size components, severely restricting their engineering applications. To address this core issue, existing technologies have mainly focused on improvements in the following aspects.
[0003] Regarding matrix reinforcement, existing technologies optimize sol-gel parameters (such as solvent-reactant ratio and catalyst dosage) to control gel crosslinking degree, or introduce heteroatoms / ceramic phases (such as boron, silicon, and metal precursors) to achieve organic-inorganic hybrid modification, thereby simultaneously improving thermal insulation and mechanical properties. For reinforcement composites, reinforcement and toughening are achieved by adding fibers (carbon fiber, ceramic fiber, organic fiber) or carbon nanomaterials. In terms of process optimization, atmospheric pressure drying is being developed to replace supercritical drying to reduce costs, or carbonization temperature is being controlled to optimize the balance between graphitization degree and thermal conductivity. Furthermore, some solutions incorporate post-processing techniques such as CO2 activation and nitrogen-oxygen gas etching to improve specific surface area and thermal insulation performance.
[0004] However, the aforementioned improvement schemes generally suffer from the following drawbacks: First, performance improvement comes at the cost of significantly increased density or substantial cost. Introducing reinforcements or hybrid modifications inevitably leads to a significant increase in material density, contradicting the lightweight nature of aerogels; post-processing techniques such as activation and etching face problems of low yield and high cost. Second, the processes are complex and time-consuming, making industrialization difficult. Existing technologies often rely on supercritical drying, complex pre-carbonization treatment, CO2 activation, or solvent replacement, which are incompatible with existing production lines. Third, density and mechanical properties remain difficult to optimize synergistically. Existing schemes often evaluate mechanical properties without considering density, lacking an evaluation perspective of "comparing comprehensive performance at the same density," resulting in limitations in the low-density range (e.g., 0.120~0.150 g / cm³). 3 The mechanical properties of ) have always been difficult to improve. When the density decreases, the strength drops sharply, while increasing the strength inevitably increases the density significantly.
[0005] Therefore, how to achieve a synergistic improvement in the mechanical and thermal insulation properties of low-density carbon aerogels without significantly increasing density or introducing complex processes, and how to develop a low-density carbon aerogel preparation method with better overall performance, simple process and industrializability at the same density, remains a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] In view of the above analysis, the present invention aims to provide a low-density carbon aerogel material and its preparation method, so as to solve at least one of the problems in the prior art, such as significantly increasing density to improve mechanical properties, complex process that is difficult to industrialize, and difficulty in synergistically optimizing mechanical properties and thermal insulation properties at low density.
[0007] The objective of this invention is achieved through the following technical solution: This invention provides a method for preparing a low-density carbon aerogel material, comprising the following steps: A compound solvent is obtained by combining two or more solvents. The phenolic resin is dissolved in the compound solvent to obtain a phenolic resin solution; A catalyst was added to the phenolic resin solution, followed by sol-gel reaction, drying, and carbonization to obtain a low-density carbon aerogel material. Wherein, the dielectric constant of the compound solvent Calculate using the following formula:
[0008] In the formula, For the first The dielectric constant of the solvent, For the first The mass fraction of the solvent, and the mass fraction of the compounded solvent. The value satisfies: 2.925 ≤ ≤2.990.
[0009] Further, the phenolic resin is a copolymer obtained by copolymerization of linear phenolic resin with a first comonomer and a second comonomer; wherein, the mass ratio of the linear phenolic resin to the total mass of the first comonomer and the second comonomer is (4~6):1, and the mass ratio of the first comonomer to the second comonomer is (5~10):1; the first comonomer is vinyltrimethoxysilane, and the second comonomer is vinyltriethoxysilane.
[0010] Furthermore, the copolymerization reaction is carried out under stirring conditions, the copolymerization reaction temperature is 60~100℃, and the copolymerization reaction time is 2~4h.
[0011] Furthermore, the catalyst is composed of sodium hydroxide, hexadecyltrimethylammonium bromide, and paraformaldehyde; The total amount of catalyst added is 5 wt.% to 25 wt.% of the mass of phenolic resin; wherein the mass ratio of sodium hydroxide, hexadecyltrimethylammonium bromide and paraformaldehyde is (8~10):(3~5):(1~2).
[0012] Furthermore, the compound solvent is mainly composed of isopropanol and contains at least one second solvent, wherein the second solvent is selected from one or more of n-propanol, ethanol, ethylene glycol, acetone, n-hexane, toluene, and methanol.
[0013] Furthermore, the mass ratio of the compounded solvents satisfies any one of the following conditions: (1) Binary system: The mass ratio of isopropanol to n-propanol is (2~4):1; (2) Binary system: The mass ratio of isopropanol to ethanol is (3~5.5):1; (3) Binary system: The mass ratio of isopropanol to ethylene glycol is (9~19):1; (4) Ternary system: The mass ratio of isopropanol, ethylene glycol and ethanol is (86.0~98.0):(1.0~7.5):(1.0~7.5).
[0014] Furthermore, the solid content of the phenolic resin solution is 12.5 wt.%~20 wt.%.
[0015] Furthermore, the sol-gel reaction is a curing reaction, with a curing temperature of 80℃~120℃ and a curing time of 12h~48h; And / or, the drying is a gradient drying: first drying at room temperature for 8-16 hours, then drying at 70-90°C for 8-16 hours; And / or, the carbonization is a gradient carbonization: heating from 20 to 35°C to 250 to 350°C at a heating rate of 1 to 3°C / min and holding for 0.5 to 3 hours, then heating from 250 to 350°C to 700 to 900°C at a heating rate of 0.5 to 2°C / min and holding for 1 to 4 hours.
[0016] This invention provides a low-density carbon aerogel material, which is prepared by the above-described method.
[0017] Furthermore, the density of the low-density carbon aerogel material is ≤0.150 g / cm³. 3 Compressive strength ≥ 0.50 MPa, thermal conductivity ≤ 0.050 W / (m·K).
[0018] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: (1) This invention achieves quantitative control of solvent polarity by combining two or more solvents and quantifying the overall polarity of the combined solvents in a logarithmic summation manner and controlling it within a suitable range. When the polarity of the combined solvents is within the suitable range, the system falls into the thermodynamically unstable region within the spinoline. Small concentration fluctuations spontaneously drive phase separation in the system, forming a highly interconnected bicontinuous interpenetrating network structure, which significantly refines and uniformly distributes the skeletal particles, fundamentally improving compressive strength and structural integrity. Existing technologies mostly remain at the level of phenomenon observation and have not established quantitative control methods for application to low-solids phenolic systems. This invention achieves a breakthrough in the comprehensive performance of low-density carbon aerogels through polarity quantification evaluation and precise control, without significantly increasing density or introducing complex processes.
[0019] (2) By controlling the polarity of the compound solvent within a suitable range, the present invention enables the sol-gel reaction to form a complete wet gel skeleton even at low solid content. It is not prone to severe shrinkage and cracking during normal pressure drying, and the uniform and fine skeleton particles enhance the network's anti-shrinkage ability. At the same time, the present invention eliminates the need for supercritical drying, activation etching, pre-carbonization treatment, and solvent replacement, significantly shortening the cycle, reducing costs, and facilitating industrialization.
[0020] (3) This invention achieves the refinement and homogenization of skeletal particles through polarity regulation. The bicontinuous interpenetrating network formed by the spinophase separation differs from the isolated "island-like" structure formed by the nucleation-growth mechanism, enabling uniform stress transmission and avoiding local failure; at the same time, the refined particles and uniform pore structure effectively suppress convective heat transfer and solid-phase heat transfer, giving the material low density, high strength, and low thermal conductivity. Unlike the conventional approach of "trading density for strength" in existing technologies, this invention achieves synergistic optimization of mechanical and thermal insulation performance within the same density range.
[0021] (4) The method for quantifying the polarity of compound solvents provided by this invention has good universality. Unlike the prior art, which is limited to trial-and-error screening of specific solvent combinations, this invention establishes a quantitative correlation between a logarithmic summation formula and a suitable polarity range. Based on the dielectric constant of different solvents, two or more solvents can be flexibly selected for compounding, as long as the overall polarity of the compounded solvent falls within the suitable range. This makes this invention not limited to a few specific solvent combinations, but allows for flexible adjustment of the compounding scheme according to raw material sources, cost control, or specific performance requirements, resulting in a wider range of applications and good industrial adaptability. Furthermore, based on this quantitative formula, the polarity of compound solvents under different ratios can be calculated in advance, guiding formulation design without extensive repeated experiments, significantly improving production efficiency and process controllability.
[0022] (5) In some preferred embodiments, the present invention further uses a copolymer obtained by copolymerizing linear phenolic resin with two vinyl silane monomers as the phenolic resin. Compared with single silane modification, the present invention introduces two vinyl silane monomers with different structures for synergistic copolymerization modification and precisely controls the proportion of each component. Single systems face a dilemma: the crosslinking points of highly reactive monomers tend to concentrate locally, while the crosslinking density of less reactive monomers is not sufficiently improved. The present invention utilizes the complementary characteristics of the two monomers in terms of reactivity: one rapidly builds the network, and the other ensures uniform distribution, so that the construction speed and uniformity of the crosslinking network can be taken into account, avoiding the defects of the single system. The two silanes and phenolic resin form an organic-inorganic hybrid network, forming Si-C or Si-OC bonds during carbonization, effectively inhibiting carbonization shrinkage and improving the mechanical strength and thermal stability of the aerogel.
[0023] (6) In some preferred embodiments, the present invention employs a ternary composite catalyst system of sodium hydroxide, cetyltrimethylammonium bromide (CTAB), and paraformaldehyde, and precisely controls the ratio of the three components. Compared with conventional alkaline catalysts or single HMTA curing agents, conventional alkaline catalysts suffer from problems such as high free alkali content, poor solubility, or ammonia release, while HMTA is difficult to disperse uniformly due to its high crystallinity and releases volatile byproducts during curing, leading to pore defects. The present invention maintains a stable weakly alkaline environment with NaOH, provides active sites to guide crosslinking, and uses paraformaldehyde as a slow-release crosslinking agent. The three components work synergistically to ensure that the crosslinking reaction proceeds uniformly in the spatial and temporal dimensions, with all components participating in the reaction and no waste generated. The improvement effect on mechanical properties is particularly significant under low-density conditions.
[0024] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0025] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0026] Figure 1 The image shows the appearance of carbon aerogel obtained by the preparation method of low-density carbon aerogel material provided in Embodiment 1 of the present invention. Figure 2 Microscopic SEM image of carbon aerogel obtained by the preparation method of low-density carbon aerogel material provided in Embodiment 3 of the present invention; Figure 3The elemental scan diagram of the carbon aerogel obtained by the preparation method of the low-density carbon aerogel material provided in Embodiment 1 of the present invention; Figure 4 The graph shows the mechanical compression test results of carbon aerogel obtained by the preparation method of low-density carbon aerogel material provided in Embodiment 3 of the present invention. Figure 5 The graph shows the mechanical compression test results of carbon aerogel obtained by the preparation method of low-density carbon aerogel material provided in Embodiment 16 of the present invention. Figure 6 The graph shows the mechanical compression test results of carbon aerogel obtained by the preparation method of low-density carbon aerogel material provided in Embodiment 4 of the present invention. Figure 7 The graph shows the mechanical compression test results of carbon aerogel obtained by the preparation method of low-density carbon aerogel material provided in Embodiment 10 of the present invention. Figure 8 The graph shows the results of the mechanical compression test of the carbon aerogel obtained in Comparative Example 5. Figure 9 The figure shows the results of the mechanical compression test of the carbon aerogel obtained in Comparative Example 9. Figure 10 The image shows a microscopic SEM image of the carbon aerogel obtained in Comparative Example 1. Detailed Implementation
[0027] Preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which form part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0028] This invention provides a method for preparing a low-density carbon aerogel material, comprising the following steps: A compound solvent is obtained by combining two or more solvents. The phenolic resin is dissolved in the compound solvent to obtain a phenolic resin solution; A catalyst was added to the phenolic resin solution, followed by sol-gel reaction, drying, and carbonization to obtain a low-density carbon aerogel material. Wherein, the dielectric constant of the compound solvent Calculate using the following formula: ; In the formula, For the first The dielectric constant of the solvent, For the first The mass fraction of the solvent, and the mass fraction of the compounded solvent. The value satisfies: 2.925 ≤ ≤2.990. n is the number of solvent types in the compound solvent, and n is a positive integer; It is the first in the compound solvent The number of the solvent, The range of values is = 1, 2, 3, ..., n. For example, in a binary system with two solvents, n=2; in a ternary system with three solvents, n=3, and so on. The dielectric constant represents the dielectric constant of the compounded solvent. For the first The mass fraction of a solvent in a compound solvent, that is, the percentage of the mass of that solvent in the total mass of the compound solvent. This means that the sum of the mass fractions of all solvents in the compound solvent is equal to 1. The above can be expanded as follows: ; For example, The values are 2.93, 2.935, 2.94, 2.945, 2.95, 2.955, 2.96, 2.965, 2.97, 2.975, 2.98, 2.985, and 2.99; the preferred values are 2.940 to 2.980.
[0029] For example, the dielectric constant of each solvent Standard values at 25°C are typically used and can be obtained from chemical handbooks or property data tables, such as the "Table of Dielectric Constants of Pure Liquids" published by the National Bureau of Standards (NBS, now NIST) in 1951. They can also be determined using existing experimental methods in the field. Compared to existing technologies, the preparation method provided by this invention, by compounding two or more solvents and quantifying the overall polarity of the compounded solvents in a logarithmic summation based on the mass fraction and dielectric constant of each solvent, controls it within a suitable range, thus achieving quantitative control of solvent polarity. This method directly affects the spiral phase separation behavior in the phenolic resin sol-gel process: when the polarity of the compounded solvent is within the suitable range, the system falls precisely into the thermodynamically unstable region within the spiral line (second derivative of free energy). 2 G / φ 2With concentrations <0, no nucleation energy barrier needs to be overcome; even minute concentration fluctuations can spontaneously, continuously, and globally increase, driving the system to spontaneously separate into solute-rich and solute-poor bicontinuous phases, ultimately forming a highly interconnected bicontinuous interpenetrating network structure. This structural feature significantly refines the size and uniform distribution of the aerogel's skeletal particles, resulting in more complete neck connections between particles and a fundamental improvement in the material's compressive strength and structural integrity. Although previous studies have focused on the influence of solvent polarity on the phenolic sol-gel process and aerogel structure, these studies have largely remained at the level of phenomenological observation and mechanistic explanation, failing to establish a quantifiable key process parameter for solvent polarity, establish quantitative control methods, and apply them to the preparation of carbon aerogels in low-solids-content phenolic systems. Under low-density conditions, due to the extreme fragility of the gel skeleton, the precision required for controlling the phase separation process is far higher than that for conventional density systems. Previous studies have failed to provide a suitable range for the polarity of the compounded solvent and its quantitative correlation with the spinotropic phase separation behavior, thus making it difficult to achieve breakthroughs in the mechanical properties of low-density carbon aerogels through active control of solvent polarity. This invention addresses the aforementioned gap by establishing a quantitative evaluation method for the polarity of compound solvents, precisely controlling it within a suitable range, and actively triggering and finely regulating the spinneret phase separation process. This achieves a breakthrough in the comprehensive performance of low-density carbon aerogels without significantly increasing density or introducing complex processes.
[0030] The preparation method provided by this invention involves compounding two or more solvents and quantifying their overall polarity, controlling it within a suitable range. This allows the sol-gel reaction to form a structurally complete wet gel framework even under low solid content conditions, preventing severe shrinkage and cracking during subsequent atmospheric pressure gradient drying. The mechanism lies in the fact that the uniform, fine framework particles formed under suitable polarity conditions enhance the shrinkage resistance of the gel network, thus solving the problems of easy cracking and difficulty in large-scale preparation during atmospheric pressure drying of low solid content systems. Furthermore, this invention eliminates the need for supercritical drying, activation or etching post-treatment, and pre-carbonization, and also avoids the time-consuming and lengthy solvent replacement steps in traditional aerogel preparation. This significantly shortens the production cycle, reduces equipment costs and operational complexity, and the process route is simple, easily compatible with existing production lines, and possesses excellent prospects for industrial production.
[0031] In the preparation method provided by this invention, the refinement and homogenization of the framework particles are achieved by compounding two or more solvents, quantifying their overall polarity, and controlling them within a suitable range. From the perspective of phase separation mechanism, the double continuous interpenetrating network structure formed by spinophase separation is fundamentally different from the "island-like" isolated particle structure formed by the nucleation-growth mechanism. The phase regions formed by spinophase separation are highly interconnected, fine in size, and uniformly distributed. This structural feature allows stress to be uniformly transmitted in the framework, avoiding local failure caused by stress concentration, thereby endowing the material with excellent mechanical properties. At the same time, the refined framework particles and uniform pore structure effectively suppress gas convection heat transfer and solid-phase heat transfer paths, enabling the material to maintain low density while also having low thermal conductivity. Unlike the conventional approach of "trading density for strength" in the prior art, this invention achieves synergistic optimization of framework strength and thermal insulation performance within the same density range through polarity control, solving the long-standing technical problem in the field that it is difficult to balance mechanical properties and thermal insulation performance at low densities.
[0032] In some embodiments, the compounded solvent is isopropanol as the main solvent and includes at least one second solvent selected from one or more of n-propanol, ethanol, ethylene glycol, acetone, n-hexane, toluene, and methanol. Isopropanol, as the main solvent, has moderate polarity (e.g., a dielectric constant of 18.3), effectively dissolving phenolic resins, while also exhibiting good miscibility with other second solvents, facilitating precise control of the overall polarity through compounding.
[0033] Specifically, the isopropanol, n-propanol, ethanol, ethylene glycol, acetone, n-hexane, toluene, methanol, etc. used in the compound solvent are all commercially available anhydrous reagents, preferably of analytical grade.
[0034] Preferably, when calculating the dielectric constant of the compounded solvent, the first... Dielectric constant of a solvent The standard values at 25℃ are used. At 25℃, the dielectric constants of each solvent are as follows: isopropanol 18.3, ethanol 24.5, ethylene glycol 37.7, methanol 32.7, n-hexane 1.88, toluene 2.24, n-propanol 20.1, and acetone 20.7.
[0035] Based on the dielectric constants of each solvent in the compound solvent at 25°C (obtained by referring to a table or through experimental measurement), the proportions of each solvent in the compound solvent can be adjusted to control the dielectric constant. This makes the compound solvent The value satisfies: 2.925 ≤ ≤2.990, ensuring that the reaction system falls precisely into the thermodynamically unstable region (second derivative of free energy) within the spinoline in subsequent processes. 2 G / φ 2 <0), without needing to overcome the nucleation energy barrier, small concentration fluctuations can spontaneously, continuously, and globally grow, driving the system to spontaneously separate into solute-rich and solute-poor bicontinuous phases, ultimately forming a highly interconnected bicontinuous interpenetrating network structure. Through quantitative control of the compound solvent, the spinneret phase separation process is actively triggered and finely regulated, thereby achieving a breakthrough in the comprehensive performance of low-density carbon aerogels without significantly increasing density or introducing complex processes.
[0036] In some embodiments, the mass ratio of the compounded solvents satisfies any one of the following conditions: (1) Binary system: Optionally, the mass ratio of isopropanol to n-propanol is (2~4):1. For example, the mass ratio of isopropanol to n-propanol is 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, 3.2:1, 3.5:1, 3.8:1, 4:1; preferably (2.5~3.5):1.
[0037] (2) Binary system: Optionally, the mass ratio of isopropanol to ethanol is (3~5.5):1. For example, the mass ratio of isopropanol to ethanol is 3:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1, 4.8:1, 5:1, 5.5:1; preferably (3.5~5.0):1.
[0038] (3) Binary system: Optionally, the mass ratio of isopropanol to ethylene glycol is (9~19):1. For example, the mass ratio of isopropanol to ethylene glycol is 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1; preferably (14~19):1.
[0039] (4) Ternary system: Optionally, the mass ratio of isopropanol, ethylene glycol and ethanol is (86.0~98.0):(1.0~7.5):(1.0~7.5). For example, the mass ratio of isopropanol, ethylene glycol and ethanol is (86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98):(1, 2, 3, 4, 5, 6, 7, 7.5):(1, 2, 3, 4, 5, 6, 7, 7.5); preferably, the mass ratio of isopropanol, ethylene glycol and ethanol is (88~92):(4~6):(4~6).
[0040] The above-mentioned compound formulation and ratio are calculated based on the aforementioned logarithmic summation formula, and the range of options is applicable to conventional phenolic resin systems and catalytic systems, demonstrating good versatility.
[0041] The preferred ratio given in this invention is a further optimized selection based on the copolymerized modified phenolic resin system and the ternary composite catalyst system of this invention. Compared with conventional phenolic resin, the resin molecular chain modified by the introduction of bissilane copolymerization in this invention has grafted silicon-oxygen structures, which changes its conformation and polar response range in solution. By further refining the control of the solvent blending ratio, it is better ensured that the polarity of the blended solvent matches the copolymerized modified resin system, thereby achieving better control of the cyclotron phase separation behavior. The above-mentioned preferred ratio is based on this system difference, so that the polarity of the blended solvent, the molecular structure characteristics of the copolymerized modified resin, and the reaction characteristics of the ternary catalyst system form a good match and synergy, thereby obtaining a carbon aerogel material with finer and more uniform skeleton particles and a more complete pore structure, further improving the mechanical properties and structural integrity of the material.
[0042] Optionally, the phenolic resin is a copolymer obtained by copolymerization of linear phenolic resin and comonomer; the comonomer is selected from at least one of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, vinyltrichlorosilane, and vinylmethyldimethoxysilane.
[0043] Optionally, the phenolic resin is a copolymer obtained by copolymerization of linear phenolic resin with a first comonomer and a second comonomer; wherein the mass ratio of the linear phenolic resin to the total mass of the first comonomer and the second comonomer is (3~6):1, and the mass ratio of the first comonomer to the second comonomer is (3~12):1; the first comonomer is vinyltrimethoxysilane, and the second comonomer is vinyltriethoxysilane.
[0044] In some preferred embodiments, the phenolic resin is a copolymer obtained by copolymerization of linear phenolic resin with a first comonomer and a second comonomer; wherein the mass ratio of the linear phenolic resin to the total mass of the first comonomer and the second comonomer is (4~6):1, and the mass ratio of the first comonomer to the second comonomer is (5~10):1; the first comonomer is vinyltrimethoxysilane, and the second comonomer is vinyltriethoxysilane.
[0045] For example, the mass ratio of the linear phenolic resin to the total mass of the first comonomer and the second comonomer is 4:1, 4.2:1, 4.5:1, 4.8:1, 5:1, 5.2:1, 5.5:1, 5.8:1, or 6:1; preferably (4.5~5.5):1.
[0046] For example, the mass ratio of the first comonomer to the second comonomer is 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, or 10:1; preferably (6~10):1.
[0047] It should be noted that this invention, based on a composite solvent system, further employs two vinyl silane monomers with different structures to synergistically copolymerize and modify linear phenolic resin. The two monomers complement each other in reactivity: one is more active to rapidly build a crosslinked network, while the other has a relatively mild hydrolysis rate to ensure uniform network distribution, thus balancing the speed and uniformity of crosslink network construction. Simultaneously, this invention ensures appropriate copolymerization reaction and sufficient network construction by precisely controlling the total ratio of linear phenolic resin to comonomers and the ratio between the two monomers. When the ratio is unbalanced, an excessively high total amount of comonomer can lead to excessive silane self-condensation, compromising system compatibility; an excessively low amount results in insufficient crosslinking density. Similarly, an unbalanced ratio between the two monomers results in uneven crosslinking point distribution due to excessive reactive monomers, and insufficient crosslinking density due to excessive inactive monomers. By controlling the ratio within an appropriate range, the two monomers can achieve better synergy. After the vinyl double bonds of the two silanes break during the copolymerization reaction, they chemically bond with the phenolic hydroxyl groups of the linear phenolic resin. Following gradient carbonization, since the initial state before carbonization is phenolic aerogel (an organic material), the phenolic resin is carbonized at high temperatures to form an organic-inorganic hybrid network linked by Si-OC bonds. The silicon-oxygen network formed by the hydrolysis and condensation of the two silanes interweaves with the phenolic organic network, further enhancing the integrity of the hybrid structure. This copolymer structure forms Si-C or Si-OC bonds during carbonization, effectively suppressing carbonization shrinkage and endowing the aerogel skeleton with stronger thermal stability and structural integrity. Thus, without significantly increasing density, the mechanical strength and thermal stability of the aerogel are further improved.
[0048] In contrast, while high-activity monomers facilitate rapid crosslinking, the crosslinking points tend to concentrate locally, leading to stress concentration. Low-activity monomers, while providing a milder crosslinking process, result in insufficient increase in crosslinking density and limited reinforcement. This invention effectively avoids these shortcomings through synergistic copolymerization of two silanes, thereby further improving the mechanical strength and thermal stability of the aerogel without significantly increasing its density.
[0049] In some preferred embodiments, the copolymerization reaction is carried out under stirring conditions, the copolymerization reaction temperature is 60~100℃, and the copolymerization reaction time is 2~4h.
[0050] For example, the copolymerization reaction temperature is 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or 100°C; preferably 70~90°C.
[0051] For example, the copolymerization reaction time is 2h, 2.25h, 2.5h, 2.75h, 3h, 3.25h, 3.5h, 3.75h, or 4h; preferably 2.5 to 3.5h.
[0052] Furthermore, in the copolymerization reaction, the stirring speed is 500 rpm to 1000 rpm, preferably 700 rpm to 800 rpm.
[0053] It should be noted that by controlling the amount of comonomer added and the reaction conditions, vinyl silane is mainly introduced into the linear phenolic resin molecular chain in the form of graft copolymerization, forming a soluble organic-inorganic hybrid copolymer. This copolymer exhibits good solubility in subsequent compounding solvents and can be uniformly dispersed, providing a uniform reaction precursor for the subsequent cycloid phase separation process. The synergistic limitation of the above conditions ensures that the copolymerization reaction proceeds fully within a suitable temperature and time window. On the one hand, this ensures that the graft copolymerization of vinyl silane monomers and linear phenolic resin achieves sufficient conversion and crosslinking density, avoiding insufficient reinforcement due to incomplete reaction. On the other hand, it prevents side reactions (such as excessive silane self-condensation, premature or uneven gelation of the system) and the network structure defects caused by excessively high temperature, excessively long time, or excessively high rotation speed. At the same time, the appropriate rotation speed ensures uniform mixing and mass transfer of the components in the reaction system at both the macroscopic and microscopic scales, allowing the two silane monomers to be evenly distributed and synergistically participate in the copolymerization, thereby obtaining a copolymer network structure with regular structure and few defects. Overall, under the above-mentioned preferred conditions, the copolymerization reaction can be carried out efficiently and controllably, so that the reinforcing effect of bissilane synergistic copolymerization can be fully utilized. The obtained phenolic copolymer resin has a higher crosslinking density and a more regular network structure, which provides a good molecular basis for the formation of a uniform skeleton in the subsequent sol-gel process, and further improves the mechanical properties and thermal stability of carbon aerogel.
[0054] In some preferred embodiments, the copolymerization reaction is carried out in an anhydrous organic solvent. Since vinylsilane monomers readily hydrolyze and condense in water to form cross-linked structures, the moisture content in the reaction system must be strictly controlled to prevent premature hydrolysis and condensation of the silane, which could affect the effective progress of the graft copolymerization reaction.
[0055] For example, the anhydrous organic solvent is selected from one or more of anhydrous ethanol, anhydrous isopropanol, anhydrous n-hexane, dichloromethane, and anhydrous acetone.
[0056] For example, the mass ratio of anhydrous organic solvent to linear phenolic resin is (3~10):1; preferably (4~6):1. If the solvent dosage is too low, the viscosity of the reaction system will be too high, which is not conducive to uniform monomer dispersion and mass transfer; if the solvent dosage is too high, the reactant concentration will decrease, the graft copolymerization rate will decrease, and the conversion rate will be insufficient. A suitable solvent dosage ensures both the homogeneity of the reaction system and good stirring and mass transfer effects, while also providing a moderate reactant concentration for the copolymerization reaction, which is beneficial for the efficient conduct of the copolymerization reaction under controllable conditions.
[0057] In some embodiments, after the copolymerization reaction is completed, the resulting product system is separated and purified. Exemplarily, the reaction solution is slowly poured into deionized water or n-hexane to precipitate the copolymer. After repeated washing to remove unreacted monomers and byproducts, the product is dried under vacuum to obtain a pure copolymer-modified phenolic resin solid. Because the degree of graft copolymerization is controlled, the obtained copolymer retains a linear or low-branched structure and exhibits good solubility. The dried copolymer solid is added to a compound solvent and dissolved completely under stirring and heating to obtain a phenolic resin solution for subsequent sol-gel reactions.
[0058] It is understood that the phenolic resin can be an unmodified linear phenolic resin or a phenolic copolymer resin that has undergone copolymerization modification. When a copolymer-modified resin is used, after the aforementioned copolymerization reaction and separation and purification steps, the resulting copolymer resin solid is dissolved in a compound solvent as described above, and can then proceed to subsequent process steps.
[0059] Specifically, dissolving the phenolic resin in the compound solvent includes the following steps: adding the phenolic resin to the compound solvent, heating and dissolving it under stirring conditions, so that the phenolic resin is fully dissolved in the compound solvent to obtain a phenolic resin solution.
[0060] For example, during the heating and dissolution process under stirring conditions, the dissolution temperature is 40-50°C, the stirring speed is 800-1000 rpm, and the dissolution time is 60-90 min. Under these conditions, the phenolic resin can be completely dissolved to form a uniform and stable resin solution, providing a homogeneous reaction precursor for subsequent catalyst dispersion and sol-gel reaction.
[0061] Optionally, when dissolving phenolic resin in a compound solvent, the mass ratio of the compound solvent to the phenolic resin is (3~7):1, so that the solid content of the phenolic resin solution is controlled in the range of 12.5wt.%~25wt.%.
[0062] Preferably, when the phenolic resin is dissolved in the compound solvent, the mass ratio of the compound solvent to the phenolic resin is (4~7):1, so that the solid content of the phenolic resin solution is controlled within the range of 12.5wt.%~20wt.% to meet the preparation requirements of low-density carbon aerogel.
[0063] More preferably, when the phenolic resin is dissolved in the compound solvent, the mass ratio of the compound solvent to the phenolic resin is (5.45~6.40):1, and the solid content of the phenolic resin solution is 13.5wt.%~15.5wt.%.
[0064] Optionally, the catalyst is selected from one or more combinations of sodium hydroxide, cetyltrimethylammonium bromide, and paraformaldehyde.
[0065] In some preferred embodiments, the catalyst consists of sodium hydroxide, hexadecyltrimethylammonium bromide, and paraformaldehyde.
[0066] Optionally, the total amount of catalyst added is 2 wt.% to 30 wt.% of the mass of phenolic resin; wherein the mass ratio of sodium hydroxide, hexadecyltrimethylammonium bromide and paraformaldehyde is (6~12):(2~6):(0.5~2.5).
[0067] Preferably, the total amount of catalyst added is 5 wt.% to 25 wt.% of the mass of phenolic resin; wherein the mass ratio of sodium hydroxide, hexadecyltrimethylammonium bromide and paraformaldehyde is (8~10):(3~5):(1~2).
[0068] For example, the total amount of catalyst added accounts for 5 wt.%, 8 wt.%, 10 wt.%, 12 wt.%, 15 wt.%, 18 wt.%, 20 wt.%, 22 wt.%, or 25 wt.% of the phenolic resin; preferably 15 wt.% to 20 wt.%.
[0069] For example, the mass ratio of sodium hydroxide, cetyltrimethylammonium bromide and paraformaldehyde is (8, 8.2, 8.5, 8.8, 9, 9.2, 9.5, 9.8, 10): (3, 3.2, 3.5, 3.8, 4, 4.1, 4.2, 4.3, 4.4, 4.5, 4.8, 5): (1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.8, 2); preferably (8.5~9.5): (4~4.5): (1~1.5).
[0070] The inventors discovered in their research that the sol-gel reaction of phenolic resins often employs conventional alkaline catalysts (such as NaOH, Ba(OH)2, NH4OH, etc.) to catalyze the phenolic condensation reaction alone, or uses the traditional curing agent hexamethylenetetramine (HMTA) to cure thermoplastic phenolic resins alone. However, all of the above catalyst systems have significant shortcomings. Among conventional alkaline catalysts, NaOH has strong catalytic activity, but the free alkali content in the resin is relatively high, affecting the material's water resistance and dielectric properties; Ba(OH)2, although having a relatively mild catalytic effect, has limited solubility and is prone to uneven distribution in the system; NH4OH decomposes and releases ammonia gas during hot pressing, which may cause the product to expand or generate internal defects. Although the traditional curing agent HMTA is currently the most widely used curing agent for thermoplastic phenolic resins, its high crystallinity makes it difficult to achieve uniform molecular-level dispersion in the resin matrix. Volatile byproducts such as ammonia released during curing easily form bubbles and pore defects inside the material, weakening the material's mechanical toughness.
[0071] To address the aforementioned issues, the ternary composite catalyst system employed in this invention effectively overcomes the limitations of existing technologies. Specifically, NaOH dissolves in an alkaline solution, providing a weakly alkaline environment suitable for sol-gel reactions; CTAB acts as a catalyst, providing nitrogen-active sites and forming N-substituted methylene bridges to promote catalytic addition condensation; phenolic resin itself is formed by the condensation reaction of phenol and formaldehyde, and the addition of paraformaldehyde provides electrophilic carbon sites (C=O) after depolymerization, further supplementing the binding of nitrogen-active sites and enhancing the cross-linking degree of the aerogel's internal framework, thereby promoting its mechanical strength. Paraformaldehyde acts as a "slow-release cross-linking agent," gradually depolymerizing and releasing formaldehyde monomers at the reaction temperature, uniformly replenishing the electrophilic carbon sites in the system, avoiding the localized overreaction and byproduct interference problems caused by the one-time decomposition and release of formaldehyde and ammonia by HMTA. Compared to existing common catalysts, the advantages of this invention are: a milder system reaction, a larger controllable range, and a significant effect on improving the mechanical properties of low-density aerogels. Furthermore, the three components, through a synergistic mechanism of "alkaline environment maintenance - active site guidance - crosslinking agent slow release," achieve homogenization of the crosslinking reaction in both spatial and temporal dimensions, effectively avoiding problems such as uneven crosslinking and interference from byproducts. When the proportions of the three components are unbalanced, excessive NaOH makes the system too alkaline, accelerating gelation and leading to structural inhomogeneity, while insufficient NaOH results in an inadequate weak alkaline environment to maintain reactivity. Excessive CTAB introduces too many surfactant molecules into the system, affecting the uniformity of the gel network, while insufficient CTAB results in insufficient active sites and limited crosslinking guidance. Excessive paraformaldehyde leads to excessively high crosslinking density and increased brittleness of the skeleton, while insufficient paraformaldehyde results in insufficient replenishment of crosslinking agents and inadequate network interconnection. Therefore, by controlling the proportions within an appropriate range, the three components can achieve optimal synergy.
[0072] In summary, unlike existing catalyst systems which commonly suffer from uneven reaction, interference from byproducts, or poor system stability, the ternary compound system of this invention exhibits a milder reaction, a wider controllable range, and complete participation in the reaction with no waste generation. Furthermore, it demonstrates a more significant improvement in mechanical properties under low-density conditions.
[0073] For example, a catalyst is added to the phenolic resin solution at 40-60°C and stirring conditions (e.g., 500-800 rpm), and stirring is continued at 40-60°C and 500-800 rpm for at least 120 minutes, such as 120-180 minutes.
[0074] In some embodiments, the sol-gel reaction is a curing reaction, with a curing temperature of 80°C to 120°C and a curing time of 12h to 48h.
[0075] For example, the curing temperature can be 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, 115℃, or 120℃; preferably 80℃~100℃. For example, the curing time can be 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h, or 48h; preferably 12h~24h. The curing temperature and curing time together determine the crosslinking rate and network formation quality of the sol-gel reaction. By controlling the curing temperature and time within the above ranges, the crosslinking reaction can be ensured to proceed at a suitable rate. If the temperature is too low or the time is too short, the crosslinking will be insufficient, and the strength of the gel skeleton will be insufficient; if the temperature is too high or the time is too long, the reaction will be too fast, which will easily lead to uneven network structure. Suitable curing conditions enable the gel network to be built gradually and uniformly, obtaining a wet gel skeleton with a complete structure and sufficient strength, providing a good foundation for drying at normal pressure.
[0076] Furthermore, the above-mentioned preferred curing conditions exhibit significant synergistic effects on the bissilane copolymer modified phenolic resin system and the ternary composite catalyst system of this invention. The grafted silica segments in the bissilane copolymer modified phenolic resin need to fully participate in the crosslinking reaction at a suitable temperature to form a uniform organic-inorganic hybrid network. The three components of the ternary catalyst system also depend on a suitable temperature window: if the temperature is too low, the paraformaldehyde depolymerization is incomplete, and the guiding effect of the CTAB active sites is limited; if the temperature is too high, the NaOH catalysis is too strong, and the crosslinking reaction is too fast, leading to structural inhomogeneity. Under the above-mentioned preferred curing conditions, the synergistic mechanism of the ternary catalyst system operates fully and stably, and the silica network of the copolymer modified resin and the phenolic organic network achieve good interpenetration and crosslinking, thereby obtaining a fully crosslinked, structurally regular aerogel framework with few defects. Combined with the ring-phase separation bicontinuous network structure established by the polarity regulation of the composite solvent, the suitable curing conditions allow this structure to be fully fixed and strengthened; the fine, uniform framework formed by the ring-phase separation is further crosslinked and enhanced during the curing process. The synergistic effect of these three factors (mixed solvent to regulate phase separation morphology, curing conditions to ensure full cross-linking of the network, and catalyst system to promote uniform curing) ensures the fine structure and mechanical strength of the low-density carbon aerogel skeleton.
[0077] In some preferred embodiments, the curing reaction is carried out using a gradient heating method. For example, a container containing a phenolic resin solution is placed in an oven and heated from room temperature (e.g., 20-35°C) to 60-80°C at a rate of 5-10°C / min, and held at this temperature for 1-2 hours; then heated to 80-100°C at a rate of 1-5°C / min, and held at this temperature for 12-24 hours; subsequently, it is naturally cooled to room temperature to obtain a wet phenolic organic gel.
[0078] The aforementioned gradient heating method is a further refinement of the curing conditions described above. The low-temperature stage allows the crosslinking reaction to start slowly, and the gel network is initially constructed and stabilized; the high-temperature stage allows the remaining active groups to react fully, increasing the crosslinking density and network integrity. This two-stage heating facilitates the gradual release of internal stress during curing, reducing the risk of cracking, and is particularly suitable for preparing low-solids-content, large-size samples. For the bissilane copolymer modified resin system of this invention, the low-temperature stage is dominated by phenolic organic crosslinking, initially fixing the bicontinuous network framework formed by the spinomeric phase separation; the high-temperature stage promotes further condensation between silane segments, making the silicon-oxygen network more complete and deeply interpenetrating with the organic network. Gradient curing allows the two crosslinking reactions to occur effectively and sequentially within different temperature windows, avoiding structural defects caused by the mismatch in the rates of the two crosslinking reactions during one-step isothermal curing.
[0079] Specifically, the drying process is gradient drying: first, drying at room temperature (e.g., 20~35℃) for 8~16 hours, and then drying at 70~90℃ for 8~16 hours.
[0080] It is understandable that the core advantage of gradient drying lies in effectively avoiding shrinkage and cracking of wet gels due to excessive capillary pressure during the drying process by controlling the solvent evaporation rate in stages. The room temperature drying stage allows the solvent to evaporate slowly, and the gel network naturally shrinks and sets under conditions without thermal stress interference; the high temperature drying stage further removes residual solvent and strengthens the framework structure through heat treatment.
[0081] Regarding the bissilane copolymer modified system and the spiral phase separation dual continuous network structure of the present invention, the present invention further optimizes the temperature and time of each stage of gradient drying to achieve a better match between the shrinkage behavior of the bissilane copolymer modified resin skeleton and the solvent evaporation rate, maximizing the retention of the fine network structure formed by spiral phase separation, thereby achieving efficient preparation of low-density aerogels under normal pressure drying conditions, and better ensuring the structural integrity and mechanical properties of the material.
[0082] In some embodiments, the carbonization is gradient carbonization, including a first carbonization stage and a second carbonization stage.
[0083] First carbonization stage: Heat from 20~35℃ (i.e., the starting temperature) to 250~350℃ (i.e., the ending temperature) at a heating rate of 1~3℃ / min and hold for 0.5~3h (i.e., the holding time).
[0084] For example, in the first carbonization stage, the heating rate is 1℃ / min, 1.5℃ / min, 2℃ / min, 2.5℃ / min, or 3℃ / min; preferably 1.5~2.5℃ / min.
[0085] For example, in the first carbonization stage, the starting temperature is 20°C, 22°C, 25°C, 28°C, 30°C, 32°C, or 35°C; preferably 25°C to 30°C.
[0086] For example, in the first carbonization stage, the termination temperature is 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, or 350°C; preferably 300°C to 350°C.
[0087] For example, in the first carbonization stage, the holding time is 0.5h, 1h, 1.5h, 2h, 2.5h, or 3h; preferably 1 to 2h.
[0088] The second carbonization stage: the temperature is increased from 250~350℃ (i.e., the starting temperature) to 700~900℃ (i.e., the ending temperature) at a heating rate of 0.5~2℃ / min, and then held at 700~900℃ for 1~4 hours (i.e., the holding time).
[0089] For example, in the second carbonization stage, the heating rate is 0.5℃ / min, 0.8℃ / min, 1℃ / min, 1.2℃ / min, 1.5℃ / min, 1.8℃ / min, or 2℃ / min; preferably 1~1.5℃ / min.
[0090] For example, in the second carbonization stage, the starting temperature is 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, or 350°C; preferably 300°C to 350°C.
[0091] For example, in the second carbonization stage, the termination temperature is 700°C, 720°C, 740°C, 750°C, 760°C, 780°C, 800°C, 820°C, 840°C, 850°C, 860°C, 880°C, or 900°C; preferably 800~850°C.
[0092] For example, in the second carbonization stage, the heat preservation time is 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, or 4h; preferably 2 to 3h.
[0093] The core advantage of gradient carbonization lies in controlling the pyrolysis process in stages, thus avoiding severe shrinkage and structural defects in the polymer caused by excessively rapid heating during carbon transformation. In the low-temperature stage (250~350℃), the temperature is raised at a slower rate and held briefly, allowing the side groups and unreacted groups in the phenolic resin to decompose gradually, and small molecule products in the crosslinked network to slowly escape, avoiding cracking and pore structure damage caused by rapid gas release. Simultaneously, the initial carbonization and shaping of the skeleton is achieved. In the high-temperature stage (700~900℃), the carbonization temperature is further increased and the holding time is extended, causing the amorphous carbon to transform into a disordered graphite structure, improving the order and mechanical strength of the carbon skeleton. At the same time, it promotes the transformation of the silicon-oxygen network into Si-C or Si-OC bonds, endowing the material with higher thermal stability and structural rigidity.
[0094] Regarding the dual silane copolymerization modified system and the spiral phase separation dual continuous network structure of the present invention, the present invention further optimizes the temperature, heating rate and holding time of each stage of gradient carbonization to achieve a better match between the skeleton shrinkage behavior and the gas escape rate during the polymer-carbon transition, maximizing the retention of the fine network structure formed by spiral phase separation. This enables the efficient preparation of low-density carbon aerogels under normal pressure carbonization conditions, and better ensures the structural integrity, mechanical properties and thermal stability of the material.
[0095] This invention also provides a low-density carbon aerogel material, prepared using the aforementioned method. The density of the low-density carbon aerogel material is ≤0.150 g / cm³. 3Compressive strength ≥ 0.50 MPa, thermal conductivity ≤ 0.050 W / (m·K).
[0096] In some embodiments, the density of the low-density carbon aerogel material is 0.120~0.150 g / cm³. 3 The compressive strength is 0.50~0.80MPa, and the thermal conductivity is 0.030~0.050 W / (m·K).
[0097] In some preferred embodiments, the density of the low-density carbon aerogel material is 0.120~0.125 g / cm³. 3 The compressive strength is 0.60~0.80MPa, and the thermal conductivity is 0.030~0.037 W / (m·K).
[0098] The raw materials used in this invention can be obtained commercially. The linear phenolic resin is a thermoplastic linear phenolic resin (Novolac / Novolak), for example, prepared by polycondensation of phenolic monomers and aldehyde monomers in the presence of an acidic catalyst, wherein the molar ratio of phenolic monomers to aldehyde monomers is 1:(0.75~0.85). The linear phenolic resin has a number-average molecular weight (Mn) of 500–5000 g / mol, preferably 500–3000 g / mol; wherein, the conventional grade has a number-average molecular weight (Mn) of 500–1200 g / mol and a degree of polymerization (n) of 4–12; the high ortho- or high molecular weight grade has a number-average molecular weight (Mn) of 1200–3000 g / mol and a degree of polymerization (n) of 12–30; the polydispersity ratio (Mw / Mn) is 1.4–2.2, and the refined narrow distribution grade has a polydispersity ratio (Mw / Mn) of 1.1–1.5; the softening point is 80–120°C, preferably 90–110°C; the free phenol content is ≤5 wt.%, and the hydroxymethyl content is ≤1 wt.%. Furthermore, the paraformaldehyde is a linear polymer of formaldehyde with the general chemical formula HO(CH2O). n H, degree of polymerization n is 8~100, preferably 8~30, formaldehyde content ≥95%, CAS number is 30525-89-4.
[0099] The linear phenolic resins used in the various embodiments and comparative examples of this invention have a number-average molecular weight Mn (GPC, polystyrene standard) of 500~1200 g / mol, a degree of polymerization n of 4~12, and a polydispersity Mw / Mn of 1.4~2.2.
[0100] The paraformaldehyde used in the various embodiments and comparative examples of this invention was purchased from Shanghai Maclean Biochemical Technology Co., Ltd., with brand name P804536 or P804537, reagent grade, 95%, CAS code: 30525-89-4, melting point 120-170°C.
[0101] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0102] Example 1: This embodiment provides a method for preparing a low-density carbon aerogel material, including the following steps: (1) A compound solvent is obtained by combining two or more solvents; In this embodiment, step (1) specifically includes: Isopropanol and n-propanol are mixed at a mass ratio of 4:1 to obtain a compound solvent. The mass fraction of isopropanol is... =4 / 5, mass fraction of n-propanol =1 / 5.
[0103] The dielectric constant of the compound solvent Calculate using the following formula:
[0104] In the formula, For the first The dielectric constant of the solvent, For the first The mass fraction of the solvent, according to the dielectric constant table, isopropanol =18.3, n-propanol =20.1. The calculated value of the compound solvent is... = (4 / 5) × ln18.3 + (1 / 5) × ln20.1 = 2.926, satisfying 2.925 ≤ ≤2.990.
[0105] Table 1. Dielectric constants of solvents (measured values at 25℃)
[0106] (2) Dissolve the phenolic resin in the compound solvent to obtain a phenolic resin solution; In this embodiment, step (2) specifically includes: The copolymerized phenolic resin was added to the compounded solvent at a mass ratio of 4:1. The mixture was stirred at 800 rpm for 90 minutes at 50°C to ensure complete dissolution of the phenolic resin, yielding a phenolic resin solution. The solid content of the phenolic resin solution was 20 wt.%.
[0107] The preparation method of the phenolic resin is as follows: Linear phenolic resin was dissolved in anhydrous ethanol at a mass ratio of 3:1, and stirred until completely dissolved. A first comonomer and a second comonomer, vinyltrimethoxysilane and vinyltriethoxysilane respectively, were added to the solution. The mass ratio of the linear phenolic resin to the total mass of the first and second comonomers was 4:1, and the mass ratio of the first and second comonomers was 10:1. The copolymerization reaction was carried out under stirring conditions at 750 rpm, 100°C, and for 2 hours. After the reaction was complete, the reaction solution was slowly poured into deionized water to precipitate the copolymer. After repeated washing to remove unreacted monomers and byproducts, the precipitate was dried under vacuum to obtain a solid copolymerized modified phenolic resin, which was used to prepare the phenolic resin solution.
[0108] (3) Add a catalyst to the phenolic resin solution, and obtain a low-density carbon aerogel material by sol-gel reaction, drying and carbonization; In this embodiment, step (3) specifically includes: A catalyst, composed of sodium hydroxide, hexadecyltrimethylammonium bromide, and paraformaldehyde, is added to the phenolic resin solution. The total amount of catalyst added is 25 wt.% of the mass of the phenolic resin; wherein the mass ratio of sodium hydroxide, hexadecyltrimethylammonium bromide, and paraformaldehyde is 8:5:2. The catalyst is added to the phenolic resin solution at 50°C and 500 rpm (e.g., in a water bath magnetic stirrer, with the temperature set to 50°C and the stirring speed to 500 rpm), and stirring continues for 120 min at 50°C and 500 rpm to obtain a phenolic resin prepolymer solution.
[0109] The phenolic resin prepolymer solution is poured into a mold and placed in an oven for curing. For example, the phenolic resin prepolymer solution is placed in a hydrothermal synthesis reactor, which is then placed in an oven. The sol-gel reaction is the curing reaction. The curing reaction is carried out using a gradient heating method: the temperature is increased from room temperature (25°C) to 80°C at a rate of 10°C / min and held for 1 hour; then increased to 120°C at a rate of 5°C / min and held for 12 hours; subsequently, it is naturally cooled to room temperature to obtain a wet phenolic organic gel. In this embodiment, no solvent replacement step is required, and the obtained wet gel is directly subjected to subsequent drying treatment.
[0110] The obtained wet phenolic organic gel was removed from the mold and dried. The drying was a gradient drying: first dried at room temperature (25°C) for 8 hours, and then dried at 90°C for 8 hours to obtain phenolic organic aerogel.
[0111] The obtained phenolic organic aerogel was placed in a horizontal tubular atmosphere furnace and carbonized under a nitrogen atmosphere, such as by introducing pure nitrogen (volume purity ≥99.995%) at a rate of 0.5 L / min. The carbonization was a gradient carbonization: the temperature was increased from 35℃ to 350℃ at a rate of 3℃ / min and held for 0.5 h, then increased from 350℃ to 900℃ at a rate of 2℃ / min and held for 1 h. After carbonization, the furnace was cooled to room temperature to obtain a low-density carbon aerogel material.
[0112] Example 2: This embodiment provides a method for preparing a low-density carbon aerogel material, including the following steps: (1) A compound solvent is obtained by combining two or more solvents; In this embodiment, step (1) specifically includes: Isopropanol and n-propanol were mixed at a mass ratio of 1:7 to obtain a compound solvent. The mass fraction of isopropanol was... =1 / 8, mass fraction of n-propanol =7 / 8.
[0113] The dielectric constant of the compound solvent Calculate using the following formula:
[0114] In the formula, For the first The dielectric constant of the solvent, For the first The mass fraction of the solvent, according to the dielectric constant table, isopropanol =18.3, n-propanol =20.1. The calculated value of the compound solvent is... =2.989, satisfying 2.925≤ ≤2.990.
[0115] (2) Dissolve the phenolic resin in the compound solvent to obtain a phenolic resin solution; In this embodiment, step (2) specifically includes: The copolymerized phenolic resin was added to the compound solvent at a mass ratio of 7:1. The mixture was stirred at 1000 rpm for 60 minutes at 40°C to ensure complete dissolution of the phenolic resin, resulting in a phenolic resin solution. The solid content of the phenolic resin solution was 12.5 wt.%.
[0116] The preparation method of the phenolic resin is as follows: Linear phenolic resin was dissolved in anhydrous ethanol at a mass ratio of 10:1, and stirred until completely dissolved. A first comonomer and a second comonomer, vinyltrimethoxysilane and vinyltriethoxysilane respectively, were added to the solution. The mass ratio of the linear phenolic resin to the total mass of the first and second comonomers was 6:1, and the mass ratio of the first and second comonomers was 5:1. The copolymerization reaction was carried out under stirring conditions at 750 rpm, 60°C, and for 4 hours. After the reaction was complete, the reaction solution was slowly poured into deionized water to precipitate the copolymer. After repeated washing to remove unreacted monomers and byproducts, the precipitate was dried under vacuum to obtain a copolymerized modified phenolic resin solid, which was used to prepare the phenolic resin solution.
[0117] (3) Add a catalyst to the phenolic resin solution, and obtain a low-density carbon aerogel material by sol-gel reaction, drying and carbonization; In this embodiment, step (3) specifically includes: A catalyst, composed of sodium hydroxide, hexadecyltrimethylammonium bromide, and paraformaldehyde, is added to the phenolic resin solution. The total amount of catalyst added is 5 wt.% of the mass of the phenolic resin; wherein the mass ratio of sodium hydroxide, hexadecyltrimethylammonium bromide, and paraformaldehyde is 10:3:1. The catalyst is added to the phenolic resin solution at 50°C and 500 rpm (e.g., in a water bath magnetic stirrer, with the temperature set to 50°C and the stirring speed to 500 rpm), and stirring continues for 120 min at 50°C and 500 rpm to obtain a phenolic resin prepolymer solution.
[0118] The phenolic resin prepolymer solution is poured into a mold and placed in an oven for curing. For example, the phenolic resin prepolymer solution is placed in a hydrothermal synthesis reactor, and then the hydrothermal synthesis reactor is placed in an oven. The sol-gel reaction is the curing reaction. The curing reaction is carried out using a gradient heating method: the temperature is increased from room temperature (25°C) to 60°C at a heating rate of 5°C / min and held for 2 hours; then the temperature is increased to 80°C at a heating rate of 1°C / min and held for 48 hours; subsequently, it is naturally cooled to room temperature to obtain a wet phenolic organic gel. In this embodiment, no solvent replacement step is required, and the obtained wet gel is directly subjected to subsequent drying treatment.
[0119] The obtained wet phenolic organic gel was removed from the mold and dried. The drying was a gradient drying: first dried at room temperature (25°C) for 16 hours, and then dried at 70°C for 16 hours to obtain phenolic organic aerogel.
[0120] The obtained phenolic organic aerogel was placed in a horizontal tubular atmosphere furnace and carbonized under a nitrogen atmosphere, such as by introducing pure nitrogen (volume purity ≥99.995%) at a rate of 0.5 L / min. The carbonization was a gradient carbonization: the temperature was increased from 20℃ to 250℃ at a rate of 1℃ / min and held for 3 hours, then increased from 250℃ to 700℃ at a rate of 0.5℃ / min and held for 4 hours. After carbonization, the furnace was cooled to room temperature to obtain a low-density carbon aerogel material.
[0121] Example 3 This embodiment provides a method for preparing a low-density carbon aerogel material, including the following steps: (1) A compound solvent is obtained by combining two or more solvents; In this embodiment, step (1) specifically includes: Isopropanol and n-propanol are mixed at a mass ratio of 2:1 to obtain a compound solvent. The mass fraction of isopropanol is... =2 / 3, mass fraction of n-propanol =1 / 3.
[0122] The dielectric constant of the compound solvent Calculate using the following formula:
[0123] In the formula, For the first The dielectric constant of the solvent, For the first The mass fraction of the solvent, according to the dielectric constant table, isopropanol =18.3, n-propanol =20.1. The calculated value of the compound solvent is... =2.938, satisfying 2.925≤ ≤2.990.
[0124] (2) Dissolve the phenolic resin in the compound solvent to obtain a phenolic resin solution; In this embodiment, step (2) specifically includes: The copolymerized phenolic resin was added to the compound solvent at a mass ratio of 6:1. The mixture was stirred at 900 rpm for 75 minutes at 45°C to ensure complete dissolution of the phenolic resin, resulting in a phenolic resin solution. The solid content of the phenolic resin solution was 14.3 wt.%.
[0125] The preparation method of the phenolic resin is as follows: Linear phenolic resin was dissolved in anhydrous ethanol at a mass ratio of 5:1, and stirred until completely dissolved. A first comonomer and a second comonomer, vinyltrimethoxysilane and vinyltriethoxysilane respectively, were added to the solution. The mass ratio of the linear phenolic resin to the total mass of the first and second comonomers was 5:1, and the mass ratio of the first and second comonomers was 8:1. The copolymerization reaction was carried out under stirring conditions at a stirring speed of 750 rpm, a reaction temperature of 80°C, and a reaction time of 3 hours. After the reaction was completed, the reaction solution was slowly poured into deionized water to precipitate the copolymer. After repeated washing to remove unreacted monomers and byproducts, the precipitate was dried under vacuum to obtain a copolymer-modified phenolic resin solid, which was used to prepare the phenolic resin solution.
[0126] (3) Add a catalyst to the phenolic resin solution, and obtain a low-density carbon aerogel material by sol-gel reaction, drying and carbonization; In this embodiment, step (3) specifically includes: A catalyst, composed of sodium hydroxide, hexadecyltrimethylammonium bromide, and paraformaldehyde, is added to the phenolic resin solution. The total amount of catalyst added is 18 wt.% of the mass of the phenolic resin; wherein the mass ratio of sodium hydroxide, hexadecyltrimethylammonium bromide, and paraformaldehyde is 9:4:1.5. The catalyst is added to the phenolic resin solution at 50°C and 500 rpm (e.g., in a water bath magnetic stirrer, with the temperature set to 50°C and the stirring speed to 500 rpm), and stirring continues for 120 min at 50°C and 500 rpm to obtain a phenolic resin prepolymer solution.
[0127] The phenolic resin prepolymer solution is poured into a mold and placed in an oven for curing. For example, the phenolic resin prepolymer solution is placed in a hydrothermal synthesis reactor, and then the hydrothermal synthesis reactor is placed in an oven. The sol-gel reaction is the curing reaction. The curing reaction is carried out using a gradient heating method: the temperature is increased from room temperature (25°C) to 70°C at a heating rate of 8°C / min and held for 1.5 hours; then the temperature is increased to 90°C at a heating rate of 3°C / min and held for 20 hours; subsequently, it is naturally cooled to room temperature to obtain a wet phenolic organic gel. In this embodiment, no solvent replacement step is required, and the obtained wet gel is directly subjected to subsequent drying treatment.
[0128] The obtained wet phenolic organic gel was removed from the mold and dried. The drying was a gradient drying: first dried at room temperature (25°C) for 12 hours, and then dried at 80°C for 12 hours to obtain phenolic organic aerogel.
[0129] The obtained phenolic organic aerogel was placed in a horizontal tubular atmosphere furnace and carbonized under a nitrogen atmosphere, such as by introducing pure nitrogen (volume purity ≥99.995%) at a rate of 0.5 L / min. The carbonization was a gradient carbonization: the temperature was increased from 25℃ to 320℃ at a heating rate of 2℃ / min and held for 1.5 h, then increased from 320℃ to 850℃ at a heating rate of 1.2℃ / min and held for 2.5 h. After carbonization, the furnace was cooled to room temperature to obtain a low-density carbon aerogel material.
[0130] Example 4 This embodiment is basically the same as Embodiment 3, except that in step (1), the mass ratio of isopropanol to n-propanol is 3:1. The calculated mass ratio of the compound solvent is... =2.930, satisfying 2.925≤ ≤2.990.
[0131] Example 5 This embodiment is basically the same as Embodiment 3, except that in step (1), the mass ratio of isopropanol to n-propanol is 1:5. The calculated mass ratio of the compound solvent is... =2.985, satisfying 2.925≤ ≤2.990.
[0132] Example 6 This embodiment is basically the same as embodiment 3, except that in step (2), when the phenolic resin is prepared, the mass ratio of the linear phenolic resin to the total mass of the first comonomer and the second comonomer is 4.2:1, and the mass ratio of the first comonomer to the second comonomer is 5.5:1.
[0133] Example 7 This embodiment is basically the same as embodiment 3, except that in step (2), when the phenolic resin is prepared, the mass ratio of the linear phenolic resin to the total mass of the first comonomer and the second comonomer is 3:1, and the mass ratio of the first comonomer to the second comonomer is 12:1.
[0134] Example 8 This embodiment is basically the same as that of embodiment 3, except that in step (2), the copolymerization reaction temperature is 95°C and the copolymerization reaction time is 3.75h.
[0135] Example 9 This embodiment is basically the same as that of embodiment 3, except that the total amount of catalyst added in step (3) is 10 wt.% of the mass of phenolic resin; wherein the mass ratio of sodium hydroxide, hexadecyltrimethylammonium bromide and paraformaldehyde is 8.5:3.5:1.8.
[0136] Example 10 This embodiment is basically the same as that of embodiment 3, except that the total amount of catalyst added in step (3) is 28 wt.% of the mass of phenolic resin; wherein the mass ratio of sodium hydroxide, hexadecyltrimethylammonium bromide and paraformaldehyde is 11:2.5:0.8.
[0137] Example 11 This embodiment is basically the same as that of embodiment 3, except that the catalyst in step (3) is composed of hexadecyltrimethylammonium bromide and paraformaldehyde, and lacks sodium hydroxide; the total amount of catalyst added is 18 wt.% of the mass of phenolic resin; wherein the mass ratio of hexadecyltrimethylammonium bromide to paraformaldehyde is 4:1.5.
[0138] Example 12 This embodiment is basically the same as that of embodiment 3, except that the catalyst in step (3) is composed of sodium hydroxide and paraformaldehyde, and lacks hexadecyltrimethylammonium bromide; the total amount of catalyst added is 18 wt.% of the mass of phenolic resin; wherein the mass ratio of sodium hydroxide to paraformaldehyde is 9:1.5.
[0139] Example 13 This embodiment is basically the same as that of embodiment 3, except that the catalyst in step (3) is composed of sodium hydroxide and hexadecyltrimethylammonium bromide and lacks paraformaldehyde; the total amount of catalyst added is 18 wt.% of the mass of phenolic resin; wherein the mass ratio of sodium hydroxide to hexadecyltrimethylammonium bromide is 9:4.
[0140] Example 14 This embodiment is basically the same as Embodiment 3, except that the compound solvent in step (1) does not contain isopropanol, but is a mixture of ethanol and n-hexane, mixed at a mass ratio of 10:1. The compound solvent is calculated to have a... =2.965, satisfying 2.925≤ ≤2.990.
[0141] Example 15 This embodiment is basically the same as embodiment 3, except that the conditions for sol-gel reaction, drying and carbonization in step (3) are different.
[0142] In this embodiment, the sol-gel reaction is a curing reaction, which is carried out using a gradient heating method: the temperature is increased from room temperature (25°C) to 60°C at a heating rate of 5°C / min and held for 2 hours; then the temperature is increased to 110°C at a heating rate of 1°C / min and held for 20 hours. The drying is a gradient drying: first, drying at room temperature (25°C) for 16 hours, then drying at 70°C for 16 hours. The carbonization is a gradient carbonization: the temperature is increased from 20°C to 280°C at a heating rate of 1°C / min and held for 2.5 hours, then the temperature is increased from 280°C to 880°C at a heating rate of 0.5°C / min and held for 1.5 hours.
[0143] Example 16 This embodiment is basically the same as Embodiment 3, except that in step (1), the compound solvent is isopropanol and ethanol, which are mixed at a mass ratio of 5:1 to obtain the compound solvent. According to the dielectric constant table, isopropanol... =18.3, ethanol =24.5. The calculated value of the compound solvent is... =2.956, satisfying 2.925≤ ≤2.990.
[0144] Example 17 This embodiment is basically the same as Embodiment 3, except that in step (1), the compound solvent is isopropanol and ethanol, which are mixed at a mass ratio of 3:1 to obtain the compound solvent. According to the dielectric constant table, isopropanol... =18.3, ethanol =24.5. The calculated value of the compound solvent is... =2.980, satisfying 2.925≤ ≤2.990.
[0145] Example 18 This embodiment is basically the same as Embodiment 3, except that in step (1), the compound solvent is isopropanol and ethanol, which are mixed at a mass ratio of 15:1 to obtain the compound solvent. According to the dielectric constant table, isopropanol... =18.3, ethanol =24.5. The calculated value of the compound solvent is... =2.925, satisfying 2.925≤ ≤2.990.
[0146] Example 19 This embodiment is basically the same as Embodiment 3, except that in step (1), the compound solvent is isopropanol and ethylene glycol, which are mixed at a mass ratio of 15:1 to obtain the compound solvent. According to the dielectric constant table, isopropanol... =18.3, ethylene glycol =37.7. The calculated value of the compound solvent is... =2.952, satisfying 2.925≤ ≤2.990.
[0147] Example 20 This embodiment is basically the same as Embodiment 3, except that in step (1), the compound solvent is isopropanol and ethylene glycol, which are mixed at a mass ratio of 9:1 to obtain the compound solvent. According to the dielectric constant table, isopropanol... =18.3, ethylene glycol =37.7. The calculated value of the compound solvent is... =2.979, satisfying 2.925≤ ≤2.990.
[0148] Example 21 This embodiment is basically the same as Embodiment 3, except that in step (1), the compound solvent is isopropanol and ethylene glycol, which are mixed at a mass ratio of 30:1 to obtain the compound solvent. According to the dielectric constant table, isopropanol... =18.3, ethylene glycol =37.7. The calculated value of the compound solvent is... =2.930, satisfying 2.925≤ ≤2.990.
[0149] Example 22 This embodiment is basically the same as Embodiment 3, except that in step (1), the compound solvent is a mixture of isopropanol, ethylene glycol, and ethanol, mixed in a mass ratio of 90:5:5 to obtain the compound solvent. According to the dielectric constant table, isopropanol... =18.3, ethylene glycol =37.7, ethanol =24.5. The calculated value of the compound solvent is... =2.958, satisfying 2.925≤ ≤2.990.
[0150] Example 23 This embodiment is basically the same as Embodiment 3, except that in step (1), the compound solvent is a mixture of isopropanol, ethylene glycol, and ethanol, mixed in a mass ratio of 86:7.5:7.5 to obtain the compound solvent. According to the dielectric constant table, isopropanol... =18.3, ethylene glycol =37.7, ethanol =24.5. The calculated value of the compound solvent is... =2.983, satisfying 2.925≤ ≤2.990.
[0151] Example 24 This embodiment is basically the same as Embodiment 3, except that in step (1), the compound solvent is a mixture of isopropanol, ethylene glycol, and ethanol, mixed in a mass ratio of 96:2:2 to obtain the compound solvent. According to the dielectric constant table, isopropanol... =18.3, ethylene glycol =37.7, ethanol =24.5. The calculated value of the compound solvent is... =2.927, satisfying 2.925≤ ≤2.990.
[0152] Comparative Examples 1-16 are basically the same as Example 1, except that the composition and ratio of the compound solvent in step (1) are detailed in Table 2.
[0153] Table 2. Composition and polarity parameters of the compound solvents in Comparative Examples 1-16
[0154] Comparative Example 17 This comparative example is basically the same as Example 1, except that the phenolic resin in step (2) is a linear phenolic resin, without the addition of the first comonomer (vinyltrimethoxysilane) and the second comonomer (vinyltriethoxysilane) for copolymerization modification. The linear phenolic resin is used directly as the phenolic resin without copolymerization modification. Correspondingly, the catalyst in step (3) is replaced with the conventional curing agent hexamethylenetetramine (HMTA). Hexamethylenetetramine is used alone as the catalyst, without the addition of sodium hydroxide, hexadecyltrimethylammonium bromide, and paraformaldehyde. The amount of hexamethylenetetramine added is 12 wt.% of the mass of the phenolic resin.
[0155] Comparative Example 18 This comparative example is basically the same as Example 1, except that the phenolic resin in step (2) is a linear phenolic resin. No first comonomer (vinyltrimethoxysilane) is added for copolymerization modification; the copolymer is obtained solely by reacting the linear phenolic resin with the second comonomer (vinyltriethoxysilane). The mass ratio of the linear phenolic resin to the second comonomer is 5:1.
[0156] Comparative Example 19 This comparative example is basically the same as Example 1, except that the phenolic resin in step (2) is a linear phenolic resin, without the addition of a second comonomer (vinyltriethoxysilane) for copolymerization modification, and the copolymer is obtained only by reacting the linear phenolic resin with the first comonomer (vinyltrimethoxysilane). The mass ratio of the linear phenolic resin to the first comonomer is 5:1.
[0157] Comparative Example 20 This comparative example is basically the same as Example 1, except that the catalyst in step (3) is triethylamine, a conventional curing agent. Triethylamine is used alone as the catalyst, and sodium hydroxide, hexadecyltrimethylammonium bromide, and paraformaldehyde are not added. The amount of catalyst added is 25 wt.% of the mass of the phenolic resin.
[0158] Comparative Example 21 This comparative example is basically the same as Example 1, except that the catalyst in step (3) is p-toluenesulfonic acid (p-TSA). P-toluenesulfonic acid is used alone as the catalyst, and sodium hydroxide, hexadecyltrimethylammonium bromide, and paraformaldehyde are not added. The amount of catalyst added is 8 wt.% of the mass of the phenolic resin.
[0159] Table 3-1 Test Results of the Examples
[0160] Table 3-2 Test Results of the Examples
[0161] Table 4. Test results of the comparative examples
[0162] The carbon aerogel materials obtained in each embodiment and comparative example were subjected to performance tests: density was determined by the water displacement method (refer to GB 1463-2005); compressive strength was tested by a universal testing machine (refer to GJB 10246.2-2021); thermal conductivity was determined by a heat flow thermal conductivity meter (refer to GB / T 10295-2008).
[0163] The morphological image of the low-density carbon aerogel material obtained in the embodiments of the present invention is shown below. Figure 1 As shown, the microscopic SEM image is as follows: Figure 2 As shown, the element scan diagram is as follows Figure 3 As shown, the mechanical compression test results are as follows: Figures 4-7 As shown.
[0164] Depend on Figure 1 As can be seen, the carbon aerogel material obtained in the embodiments of the present invention has a complete appearance and no cracks, and can be used to prepare large-sized blocks and products.
[0165] according to Figure 2 The carbon aerogel particles obtained in the embodiments of the present invention are generally small and uniform in size. The aerogel skeleton is composed of particles with relatively uniform size, which are interconnected to form a continuous three-dimensional network structure, ultimately forming a porous network structure with a relatively uniform particle size distribution; and from Figure 10 It can be seen that the carbon aerogel particles obtained in the comparative example are generally larger, and some particles are also larger and of varying sizes. Through comparison, it can be shown that the carbon aerogel obtained in the embodiments of the present invention is superior to the comparative example in terms of the fineness of the skeletal particles, the uniformity of particle size distribution, the adequacy of interparticle connections, and the continuity and integrity of the network structure.
[0166] Figure 3 The EDS elemental distribution results show that Si elements are distributed continuously or quasi-continuously along the three-dimensional carbon framework and intertwine with the C element distribution area. No obviously isolated Si enriched particles are observed, indicating that the silicon source-derived phase has good spatial continuity in the carbon framework, further proving that the carbon aerogel obtained in this invention has a double continuous interpenetrating structure.
[0167] according to Figures 4 to 9 The compressive stress-strain curves of the low-density carbon aerogels obtained in the embodiments of the present invention show significantly higher compressive strength and better mechanical load-bearing properties compared to the comparative examples. For example, from... Figure 4 It can be seen that in Example 3, the compressive strength (i.e., peak stress) reaches 0.79 MPa when the strain reaches approximately 3%, which is much higher than the 0.33 MPa of Comparative Example 9 (e.g., ...). Figure 9 As shown in the figure, this invention, through the polarity control of the compound solvent, can construct a double continuous interpenetrating network structure, which can effectively refine the aerogel skeleton particles and enhance the inter-particle connections, enabling the aerogel material to maintain higher load-bearing capacity and structural stability under low-density conditions. In contrast, from Figure 9As can be seen, Comparative Example 9 entered a clear compression plateau after the stress reached 0.33 MPa, indicating that its skeleton had lower load-bearing efficiency, and that local buckling and pore structure collapse were more pronounced. Therefore, the embodiments of the present invention achieve a significant improvement in compressive strength in a lower density range, with a stronger aerogel skeleton and significantly better mechanical properties than the comparative example, fully demonstrating the significant advantages of the present invention in the synergistic optimization of the mechanical properties of low-density carbon aerogels.
[0168] Compared to preparation methods using a single solvent, the embodiments of this invention precisely control the polarity of the system to a suitable range by using a compound solvent, actively triggering spinomeric phase separation to form a highly interconnected bicontinuous interpenetrating network structure, resulting in significantly refined and uniformly distributed skeletal particles. Under similar density conditions, the carbon aerogel obtained in the embodiments of this invention exhibits significantly better compressive strength than the single solvent system, effectively improving mechanical properties at low densities, while avoiding complex processes such as supercritical drying and solvent replacement, demonstrating promising prospects for industrial applications.
[0169] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a low-density carbon aerogel material, characterized in that, Includes the following steps: A compound solvent is obtained by combining two or more solvents. The phenolic resin is dissolved in the compound solvent to obtain a phenolic resin solution; A catalyst was added to the phenolic resin solution, followed by sol-gel reaction, drying, and carbonization to obtain a low-density carbon aerogel material. Wherein, the dielectric constant of the compound solvent Calculate using the following formula: In the formula, For the first The dielectric constant of the solvent, For the first The mass fraction of the solvent, and the mass fraction of the compounded solvent. The value satisfies: 2.925 ≤ ≤2.
990.
2. The preparation method according to claim 1, characterized in that, The phenolic resin is a copolymer obtained by copolymerization of linear phenolic resin with a first comonomer and a second comonomer; wherein the mass ratio of the linear phenolic resin to the total mass of the first comonomer and the second comonomer is (4~6):1, and the mass ratio of the first comonomer to the second comonomer is (5~10):1; the first comonomer is vinyltrimethoxysilane, and the second comonomer is vinyltriethoxysilane.
3. The preparation method according to claim 2, characterized in that, The copolymerization reaction is carried out under stirring conditions, with a copolymerization temperature of 60~100℃ and a copolymerization time of 2~4h.
4. The preparation method according to claim 1, characterized in that, The catalyst is composed of sodium hydroxide, hexadecyltrimethylammonium bromide and paraformaldehyde; The total amount of catalyst added is 5 wt.% to 25 wt.% of the mass of phenolic resin; wherein the mass ratio of sodium hydroxide, hexadecyltrimethylammonium bromide and paraformaldehyde is (8~10):(3~5):(1~2).
5. The preparation method according to claim 1, characterized in that, The compound solvent is mainly composed of isopropanol and contains at least one second solvent, which is selected from one or more of n-propanol, ethanol, ethylene glycol, acetone, n-hexane, toluene, and methanol.
6. The preparation method according to claim 5, characterized in that, The mass ratio of the compound solvents satisfies any one of the following conditions: (1) Binary system: The mass ratio of isopropanol to n-propanol is (2~4):1; (2) Binary system: The mass ratio of isopropanol to ethanol is (3~5.5):1; (3) Binary system: The mass ratio of isopropanol to ethylene glycol is (9~19):1; (4) Ternary system: The mass ratio of isopropanol, ethylene glycol and ethanol is (86.0~98.0):(1.0~7.5):(1.0~7.5).
7. The preparation method according to claim 1, characterized in that, The solid content of the phenolic resin solution is 12.5 wt.% to 20 wt.%.
8. The preparation method according to claim 1, characterized in that, The sol-gel reaction is a curing reaction, with a curing temperature of 80℃~120℃ and a curing time of 12h~48h; And / or, the drying is a gradient drying: first drying at room temperature for 8-16 hours, then drying at 70-90°C for 8-16 hours; And / or, the carbonization is a gradient carbonization: heating from 20 to 35°C to 250 to 350°C at a heating rate of 1 to 3°C / min and holding for 0.5 to 3 hours, then heating from 250 to 350°C to 700 to 900°C at a heating rate of 0.5 to 2°C / min and holding for 1 to 4 hours.
9. A low-density carbon aerogel material, characterized in that, It is prepared by any one of the preparation methods described in claims 1 to 8.
10. The low-density carbon aerogel material according to claim 9, characterized in that, The density of the low-density carbon aerogel material is ≤0.150 g / cm³. 3 Compressive strength ≥ 0.50 MPa, thermal conductivity ≤ 0.050 W / (m·K).
